EFFICIENCY OF THE COMBINED APPLICATION OF RADIOFREQUENCY AND ENDOVENOUS LASER ABLATION OF VEINS IN THE TREATMENT OF VARICOSE DISEASE OF THE LOWER EXTREMITIES - Goshchynsky, V. B.; Migenko, B. O. (Здобутки клінічної і експериментальної медицини, 2023)
Radiofrequency ablation (RFA) and endovenous laser coagulation of veins (EVLC) are of priority in the treatment of varicose veins of the lower extremities in outpatient settings. Although the indications for these operations and the technology of their application are defined, the issue of improving their functional results, in particular the involution of collateral veins on the lower leg after ablation of the great saphenous vein, is relevant. The aim – to improve the results of the treatment of varicose veins in an outpatient setting by using a combination of radiofrequency and laser vein ablation. Material and Methods. Under observation were 154 patients who were operated on with the help of RFA and 111 patients who underwent combined thermal ablation GSV RFA (on the thigh) and EVLС (on the leg). To compare the effectiveness of RFA and the combination of RFA with EVLС (hybrid thermoablation of veins), a quantitative and qualitative assessment of their results was carried out. In particular, the quantitative assessment was performed using a number of scales VCSS, VDS, VSDS, VSS. Questionnaires: MOS SF–36 and CIVIQ–20 were used for qualitative assessment. The results of operations were evaluated after 3, 6 months and a year after their implementation. Results. The analysis of the results of operations shows that, according to quantitative and qualitative indicators, combined operations with the simultaneous use of RFA and EVLС are more effective than RFA. These indicators were directly influenced by the number of residual veins after 6 months of observation (33.1 % after RFA and 5.4 % after hybrid thermoablation). Conclusion. The use of hybrid thermal ablation for the treatment of varicose veins of the lower extremities, in outpatient conditions, is qualitatively and quantitatively more effective than RFA.